 Suggested languages for you:

Europe

Answers without the blur. Sign up and see all textbooks for free! Q15E

Expert-verified Found in: Page 249 ### Fundamentals Of Differential Equations And Boundary Value Problems

Book edition 9th
Author(s) R. Kent Nagle, Edward B. Saff, Arthur David Snider
Pages 616 pages
ISBN 9780321977069 # In Problems 3 – 18, use the elimination method to find a general solution for the given linear system, where differentiation is with respect to t.$\frac{\mathbf{dw}}{\mathbf{dt}}{\mathbf{=}}{\mathbf{5}}{\mathbf{w}}{\mathbf{+}}{\mathbf{2}}{\mathbf{z}}{\mathbf{+}}{\mathbf{5}}{\mathbf{t}}{\mathbf{,}}\phantom{\rule{0ex}{0ex}}\frac{\mathbf{dz}}{\mathbf{dt}}{\mathbf{=}}{\mathbf{3}}{\mathbf{w}}{\mathbf{+}}{\mathbf{4}}{\mathbf{z}}{\mathbf{+}}{\mathbf{17}}{\mathbf{t}}$

The solutions for the given linear system are $w\left(t\right)=-\frac{2}{3}{c}_{1}{e}^{2t}+{c}_{2}{e}^{7t}+t+1$ and $z\left(t\right)={c}_{1}{e}^{2t}+{c}_{2}{e}^{7t}-2-5t$.

See the step by step solution

## Step 1: General form

Elimination Procedure for 2 × 2 Systems

To find a general solution for the system

${\mathbf{L}}_{\mathbf{1}}\left[\mathbf{x}\right]\mathbf{+}{\mathbf{L}}_{\mathbf{2}}\left[\mathbf{y}\right]\mathbf{=}{\mathbf{f}}_{\mathbf{1}}\mathbf{,}\phantom{\rule{0ex}{0ex}}{\mathbf{L}}_{\mathbf{3}}\left[\mathbf{x}\right]\mathbf{+}{\mathbf{L}}_{\mathbf{4}}\left[\mathbf{y}\right]\mathbf{=}{\mathbf{f}}_{\mathbf{2}}\mathbf{,}$

Where ${\mathbf{L}}_{\mathbf{1}}\mathbf{,}{\mathbf{L}}_{\mathbf{2}}\mathbf{,}{\mathbf{L}}_{\mathbf{3}}\mathbf{,}$ and ${\mathbf{L}}_{\mathbf{4}}$ are polynomials in $D=\frac{d}{dt}$

a. Make sure that the system is written in operator form.

b. Eliminate one of the variables, say, y, and solve the resulting equation for. If the system is degenerating, stop! A separate analysis is required to determine whether or not there are solutions.

c. (Shortcut) If possible, use the system to derive an equation that involves but not its derivatives. [Otherwise, go to step (d).] Substitute the found expression for into this equation to get a formula for. The expressions for, and give the desired general solution.

d. Eliminate x from the system and solve for. [Solving for gives more constants----in fact, twice as many as needed.]

e. Remove the extra constants by substituting the expressions for and into one or both of the equations in the system. Write the expressions for and in terms of the remaining constants.

## Step 2: Evaluate the given equation

Given that,

$\frac{dw}{dt}=5w+2z+5t ......\mathbf{\left(}\mathbf{1}\mathbf{\right)}\phantom{\rule{0ex}{0ex}}\frac{dz}{dt}=3w+4z+17t ......\mathbf{\left(}\mathbf{2}\mathbf{\right)}$

Let us rewrite the system in operator form,

$\left(D-5\right)\left[w\right]-2z=5t ......\mathbf{\left(}\mathbf{3}\mathbf{\right)}\phantom{\rule{0ex}{0ex}}-3w+\left(D-4\right)\left[z\right]=17t ......\mathbf{\left(}\mathbf{4}\mathbf{\right)}$

Multiply 3 on equation (3) and D-5 on both sides of equation (4) then add equation (3) and (4) together one gets,

$3\left(D-5\right)\left[w\right]-6z-3\left(D-5\right)w+\left(D-5\right)\left(D-4\right)\left[z\right]=15t+\left(D-5\right)17t\phantom{\rule{0ex}{0ex}}-6z\left({D}^{2}-4D-5D+20\right)\left[z\right]=15t+17-85t\phantom{\rule{0ex}{0ex}}\left({D}^{2}-9D+14\right)\left[z\right]=17-70t\phantom{\rule{0ex}{0ex}}\left({D}^{2}-9D+14\right)\left[z\right]=17-70t ......\mathbf{\left(}\mathbf{5}\mathbf{\right)}$

Since the auxiliary equation to the corresponding homogeneous equation is: ${r}^{2}-9r+14=0$

. The roots are r=7 and r=2.

Then, the homogeneous solution of u is:

${z}_{h}\left(t\right)={c}_{1}{e}^{2t}+{c}_{2}{e}^{7t} ......\mathbf{\left(}\mathbf{6}\mathbf{\right)}$

Let us take the undetermined coefficients and assume that

${z}_{p}\left(t\right)=A+Bt ......\mathbf{\left(}\mathbf{7}\mathbf{\right)}$

Now derivate the equation (7)

$D\left[{z}_{p}\left(t\right)\right]=B\phantom{\rule{0ex}{0ex}}{D}^{2}\left[{z}_{p}\left(t\right)\right]=0$

## Step 3: Substitution method

Substitute the derivation in equation (5).

$\left({D}^{2}-9D+14\right)\left[A+Bt\right]=17-70t\phantom{\rule{0ex}{0ex}}{D}^{2}\left[A+Bt\right]-9D\left[A+Bt\right]+14\left[A+Bt\right]=17-70t\phantom{\rule{0ex}{0ex}}0-9B+14A+14Bt=17-70t\phantom{\rule{0ex}{0ex}}-9B+14A+14Bt=17-70t$

Now, equalize the like terms.

$-9B+14A=17\phantom{\rule{0ex}{0ex}}14B=-70\phantom{\rule{0ex}{0ex}}B=\frac{-70}{14}=-5$

Then,

$-9\left(-5\right)+14A=17\phantom{\rule{0ex}{0ex}}45+14A=17\phantom{\rule{0ex}{0ex}}14A=17-45\phantom{\rule{0ex}{0ex}}A=\frac{-28}{14}=-2$

So, ${z}_{p}\left(t\right)=-2-5t ......\mathbf{\left(}\mathbf{8}\mathbf{\right)}$

Use equations (6) and (8) to get,

$z\left(t\right)={z}_{h}\left(t\right)+{z}_{p}\left(t\right)\phantom{\rule{0ex}{0ex}}z\left(t\right)={c}_{1}{e}^{2t}+{c}_{2}{e}^{7t}-2-5t ......\mathbf{\left(}\mathbf{9}\mathbf{\right)}$

Now, take equation (4).

$-3w+\left(D-4\right)\left[z\right]=17t\phantom{\rule{0ex}{0ex}}-3w=17t-\left(D-4\right)\left[z\right]\phantom{\rule{0ex}{0ex}}w=\frac{1}{3}\left(D-4\right)\left[z\right]-\frac{17}{3}t\phantom{\rule{0ex}{0ex}}=\frac{1}{3}\left(D-4\right)\left[{c}_{1}{e}^{2t}+{c}_{2}{e}^{7t}-2-5t\right]-\frac{17}{3}t$

$=\frac{1}{3}\left(2{c}_{1}{e}^{2t}+7{c}_{2}{e}^{7t}-5-4\left({c}_{1}{e}^{2t}+{c}_{2}{e}^{7t}-2-5t\right)\right)-\frac{17}{3}t\phantom{\rule{0ex}{0ex}}=\frac{2{c}_{1}{e}^{2t}}{3}+\frac{7{c}_{2}{e}^{7t}}{3}-\frac{5}{3}-\frac{4{c}_{1}{e}^{2t}}{3}-\frac{4{c}_{2}{e}^{7t}}{3}+\frac{8}{3}+\frac{20t}{3}-\frac{17t}{3}\phantom{\rule{0ex}{0ex}}=-\frac{2}{3}{c}_{1}{e}^{2t}+{c}_{2}{e}^{7t}+t+1$

So, the solution is founded.

## Recommended explanations on Math Textbooks

94% of StudySmarter users get better grades. 